2020
DOI: 10.3390/atmos11090907
|View full text |Cite
|
Sign up to set email alerts
|

Dissolved and Suspended Forms of Metals and Metalloids in Snow Cover of Megacity: Partitioning and Deposition Rates in Western Moscow

Abstract: Concentrations and ratio of dissolved and suspended forms of metals and metalloids (MMs) in snow cover and their deposition rates from the atmosphere in the western part of Moscow were studied. Forms of MMs were separated using a filter with pore diameter of 0.45 μm; their concentrations were measured by ICP-MS and ICP-AES methods. Anthropogenic impact in Moscow caused a significant increase in dust load (2–7 times), concentration of solid particles in snow cover (2–5 times), and mineralization of snow meltwat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 107 publications
1
28
0
Order By: Relevance
“…This indicates the significant role of wet deposition processes for the PTEs input into terrestrial landscapes. The main sources of most of these PTEs are vehicle emissions, fuel combustion, tires and brake pads wear, road surface abrasion, roadside soil particles blowing, industrial enterprises emissions, as well as macroregional long-distance transport of pollutants (Demetriades and Birke 2015;Grigoratos and Martini 2015;Grivas et al 2018;Konstantinova et al 2020;Liyandeniya et al 2020;Logiewa et al 2020;Orlović-Leko et al 2020;Ramírez et al 2020;Seleznev et al 2020;Tian et al 2020), which is confirmed by the previously identified sources of snow cover pollution in the western part of Moscow (Vlasov et al 2020). The remaining PTEs on the territory of the MO MSU were apparently of mixed anthropogenic-terrigenous sources (P 38 , Ba 31 , As 30 , W 22 , Mn 20 , Sn 19 , Na 16 , Co 14 , Ni 12 , Be 11 , K 11 ) and terrigenous origin (Rb 6 , Cr 4 , Fe 3 ), which indicates the influence of solid particles blown out from the Earth's surface and included in the atmospheric precipitation.…”
Section: Sources Of Ptes In Rainwatersupporting
confidence: 55%
See 1 more Smart Citation
“…This indicates the significant role of wet deposition processes for the PTEs input into terrestrial landscapes. The main sources of most of these PTEs are vehicle emissions, fuel combustion, tires and brake pads wear, road surface abrasion, roadside soil particles blowing, industrial enterprises emissions, as well as macroregional long-distance transport of pollutants (Demetriades and Birke 2015;Grigoratos and Martini 2015;Grivas et al 2018;Konstantinova et al 2020;Liyandeniya et al 2020;Logiewa et al 2020;Orlović-Leko et al 2020;Ramírez et al 2020;Seleznev et al 2020;Tian et al 2020), which is confirmed by the previously identified sources of snow cover pollution in the western part of Moscow (Vlasov et al 2020). The remaining PTEs on the territory of the MO MSU were apparently of mixed anthropogenic-terrigenous sources (P 38 , Ba 31 , As 30 , W 22 , Mn 20 , Sn 19 , Na 16 , Co 14 , Ni 12 , Be 11 , K 11 ) and terrigenous origin (Rb 6 , Cr 4 , Fe 3 ), which indicates the influence of solid particles blown out from the Earth's surface and included in the atmospheric precipitation.…”
Section: Sources Of Ptes In Rainwatersupporting
confidence: 55%
“…Blown-out soil particles are also a source of P in atmospheric aerosols and precipitation (Bencharif-Madani et al 2019). Deicing agents can supply Na and Ca, since CaCl 2 and marble chips (Ca, Mg)CO 3 are among the main deicing agents after NaCl in Moscow (Vlasov et al 2020). (Song and Gao 2011).…”
Section: Sources Of Ptes In Rainwatermentioning
confidence: 99%
“…Field observation, laboratory-experimental, and modeling studies are included, along with environmental monitoring and source apportionment research of local, regional, or global relevance. The fieldwork covered in the articles was conducted in various types of locations: urban sites (e.g., the cities of Chengdu, Gucheng [1], Helsinki [2], Montreal [3], and Moscow [4]); small cities and rural areas (e.g., Yulin, Huimin, and Zhengzhou [1], Tien Shan [5], Valday [6], and "36 sites on a 2800 km submeridional profile from the city of Barnaul to Salekhard" [7]); industrial [6]; remote (e.g., the Arctic, Antarctic [8], and Tibetan Plateau [9]); and other locations (e.g., along highways [10] and in the mountains [11]).…”
mentioning
confidence: 99%
“…The articles collected in this Special Issue focus on the following aspects of the interaction of air pollution with snow and the effects of seasonality: (1) the impact of deposited air pollutants on the snow albedo [2,11,12], (2) the composition and properties of particulate and volatile air pollutants detected in snow [4,7,8,11], (3) links with the sources and impact assessment, including, more specifically, seasonality of black carbon in the air and snow [1,2,5,9,12], (4) metals and metalloids in snow [4,6], (5) radioactive isotopes in snow [10], (6) snowpack pollution as an indicator of atmospheric pollution [1,[6][7][8]10,12], (7) photochemistry of compounds released due to interactions with anthropogenic particles that became mixed with snow [3], and (8) the effect of snow on greenhouse gas fluxes from the underlying peat [13].…”
mentioning
confidence: 99%
See 1 more Smart Citation